2004
DOI: 10.1023/b:gene.0000019939.38428.e5
|View full text |Cite
|
Sign up to set email alerts
|

C-banding Pattern and Nucleolar Organizer Regions of Amphioxus Branchiostoma belcheri tsingtauense Tchang et Koo, 1936

Abstract: Chromosome banding study remains lacking in amphioxus heretofore. This paper reports the C-band pattern of the metaphase chromosomes of amphioxus Branchiostoma belcheri tsingtauense, the first description of banded karyotype in cephalochordate. The C-banding showed that around 50% of the second chromosome pair examined was heteromorphic, while the remaining ones were homomorphic. In contrast, the other 17 pairs were all homomorphic. These broadly support our previous suggestion that the second chromosome pair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The karyotype of B. japonicum (quoted in the paper as B. belcheri ), the sole species for which a good morphological resolution was obtained, showed very small-sized (under 3 μm), mostly acrocentric chromosomes with only 1 or 2 biarmed pairs ( fig. 2 A) [Zhang et al, 2004]. This observation fits well with the small amount of DNA for the haploid genome, corresponding to 0.59 pg/n (http://www.genomesize.com).…”
Section: Genome Sizes and Cytogenetics Of Nonvertebrate Chordatessupporting
confidence: 79%
See 3 more Smart Citations
“…The karyotype of B. japonicum (quoted in the paper as B. belcheri ), the sole species for which a good morphological resolution was obtained, showed very small-sized (under 3 μm), mostly acrocentric chromosomes with only 1 or 2 biarmed pairs ( fig. 2 A) [Zhang et al, 2004]. This observation fits well with the small amount of DNA for the haploid genome, corresponding to 0.59 pg/n (http://www.genomesize.com).…”
Section: Genome Sizes and Cytogenetics Of Nonvertebrate Chordatessupporting
confidence: 79%
“…C-band heterochromatin is not only present in most centromeric and terminal regions but also in some interstitial regions, occupying about 54.3% of the chromosome surface that appeared highly heterochromatinized ( fig. 2 A) [Zhang et al, 2004]. In B. japonicum , there was a single pair of telomerically located Ag-NORs [Zhang et al, 2004], confirmed by FISH with 18S rDNA probe [Castro and Holland, 2002].…”
Section: Genome Sizes and Cytogenetics Of Nonvertebrate Chordatesmentioning
confidence: 75%
See 2 more Smart Citations
“…All of these restrict the progress in the study of amphioxus chromosome and consequently, only the chromosome numbers of three lancelets were available for a long period. Until 2002, Castro & Holland firstly used amphioxus embryos to prepare metaphase spreads, which led to the new achievements in the karyotype (Wang et al, 2003), banding pattern Zhang et al, 2004) and gene mapping (Castro & Holland, 2002Castro et al, 2004;Luke et al, 2003;Minguillón et al, 2004).…”
mentioning
confidence: 99%